2020
DOI: 10.1101/2020.07.02.20145177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Detection in Sewage in Santiago, Chile - Preliminary results

Abstract: The detection of viruses in sewage is a method of environmental surveillance, which allows evaluating the circulation of different viruses in a community. This study presents the first results of sewage surveillance to detect the circulation of SARS-CoV-2 virus in Santiago, Chile. Using ultracentrifugation associated with RT-qPCR, we detected SARS-CoV-2 in untreated and treated wastewater samples obtained two treatment plants, which together process around 85% of the wastewater from the city. This is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 11 publications
1
35
0
3
Order By: Relevance
“…Although there is a lack of studies on the presence of SARS-CoV-2 in wastewater, the detection of viral RNA (ribonucleic acid) in wastewater samples has gained considerable attention based on the idea of wastewater-based surveillance to detect community spread. As per the aim and scope of the present study, 34 works (eight research articles ( Table 1 ) and 26 pre-print articles [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ]) are included to understand the applicability of wastewater-based surveillance.…”
Section: Presence Of Coronavirus In Wastewater and Wastewater-based Smentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a lack of studies on the presence of SARS-CoV-2 in wastewater, the detection of viral RNA (ribonucleic acid) in wastewater samples has gained considerable attention based on the idea of wastewater-based surveillance to detect community spread. As per the aim and scope of the present study, 34 works (eight research articles ( Table 1 ) and 26 pre-print articles [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ]) are included to understand the applicability of wastewater-based surveillance.…”
Section: Presence Of Coronavirus In Wastewater and Wastewater-based Smentioning
confidence: 99%
“…They also observed that quantified RNA concentration was correlated (when adjusted for time lag) with the epidemiological curve (R 2 value of 0.99) and the number of admissions in local hospital (R 2 values of 0.99). Ampuero et al [ 20 ] attempted to detect the circulation of SARS-CoV-2 by sewage surveillance of two WWTPs serving 85 % of the wastewater generated in Santiago, Chile. When the cases of COVID-19 were low, SARS-CoV-2 RNA was not detected in wastewater.…”
Section: Presence Of Coronavirus In Wastewater and Wastewater-based Smentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional wastewater treatment process (normally the activated sludge process) should be good enough to inactivate SARS-CoV-2. In contrast, some studies reported that the positive results for viral RNA in effluent could still be discovered even after WWTP treatment [25] , [44] . The possible reasons to explain these contradictory results are the lack of a standardized procedure of SARS-CoV-2 RNA detection in wastewater, and the various treatment techniques adopted in different WWTPs at reality environmental conditions.…”
Section: Characteristics Of Coronaviruses In Aqueous Environmentmentioning
confidence: 99%
“…Recently, large numbers of investigations have reported that the RNA of SARS-CoV-2 has been detected in raw sewage, secondary treated wastewater (normally biological wastewater treatment process being applied), and even the non-potable water used for urban irrigation ( Fig. 2 ) [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . More importantly, the infectious virus has also been detected in feces and urine of patients [45] , [46] , [47] , which triggered the public’s high concern about fecal-oral transmission and/or wastewater transmission.…”
Section: Introductionmentioning
confidence: 99%